Michelle Alfano on Her Memoir, The Unfinished Dollhouse - Cusmano, Liana (Italian Canadiana, 2020)
Liana Cusmano’s interview with Toronto author Michelle Alfano offers reflections on gender identity and living through a child’s transitioning. The act of writing helped Alfano overcome the distress she felt during this difficult time. In her memoir The Unfinished Dollhouse, Michelle Alfano recounts the journey she underwent in accepting and embracing her son’s transgender identity. From tell-tale signs in early childhood and the mental and physical afflictions in the early teen years, to the reactions of family and friends and the final steps in a social and medical transition from female to male, Alfano explores the thoughts and feelings she experienced over the years as her son, River, fought to be his truest self.